Labour market institutions in Hungary with a focus on wage and employment flexibility - Hedvig Horváth; Zoltán Szalai (Magyar Nemzeti Bank, 2008)
It is widely believed today, that the operation of the labour markets is influenced by institutional factors, affecting macroeconomic adjustment in response to shocks. In this way, labour market institutions affect both cyclical and long-term growth and inflation performance of an economy. The aim of our paper is to review the operation of Hungarian labour market institutions from the point of view of labour market flexibility and find its place in international comparison in the light of existing stock of knowledge on the subject. We describe the institutional setup of the labour markets through seven dimensions (unemployment generosity, tax wedge, active labour market policies, employment protection legislation, product market regulation, union density and coverage and wage bargaining institutions) for which internationally comparable data are available. We conclude that the Hungarian labour market institutions are rather flexible in EU-comparison. However, tax wedge is high and the active labour market policies still perform poorly, both contributing to weak employment.
Keywords: J31; J51; K20; L43; 330; wage flexibility; unemployment; labour market institutions; product market regulation; policy complementarity; Arbeitsmarkt; Arbeitsmarktpolitik; Arbeitsmarktflexibilität; Arbeitslosigkeit; Ungarn